The mediating and moderating role of neighbourhoods and regions on second-generation immigrant youths' school-to-work transitions in the Netherlands - Weßling, Katarina [Verfasser]; Meng, Christoph [Verfasser] (My University, 2021)
"Contexts in which people live such as neighbourhoods, cities or regions influence individuals. However, research analysing effects of different contexts simultaneously is limited. Our paper's focus is to examine the interrelation between regional and neighbourhood conditions and their influence on school-to-work transitions. We investigate the process of transitioning from vocational training to employment, with a specific focus on adolescents from non-Western immigrant origin. We link Dutch survey data on almost 15,000 graduates with spatial information from Statistics Netherlands and compare results across multilevel linear probability models. Overall, we find employment prospects to be reduced in neighbourhoods and regions that are socioeconomically unfavourable. However, neighbourhood influences diminish or even disappear once accounted for the region. Deprived conditions in urban regions are particularly detrimental for adolescents of immigrant descent. However, a high share of coethnics in the neighbourhood reduces the unemployment risk of second-generation non-Western minorities in deprived urban regions. This finding stresses the relevance of immigrants' neighbourhood networks for education and employment prospects." (authors' abstract; BIBB-Doku)
Keywords: G 1.3.2.2 Übergänge; P 1.5 Migranten; I 2.2.1 Westeuropa; Berufseinmündung; Migrant; Zweite Generation; Sozialraum; Regionale Herkunft; Einflussfaktor; Arbeitsmarktchance; Niederlande